Second Generation Zwitterionic Aza-Diarylethene: Photoreversible CN Bond Formation, Three-State Photoswitching, Thermal Energy Release, and Facile Photoinitiation of Polymerization - Sacherer, Maximilian-Tobias; Dube, Henry (Angewandte Chemie International Edition, 2024)
Diarylethenes are a well-studied and optimized class of photoswitches with a wide range of applications, including data storage, smart materials, or photocontrolled catalysis and biological processes. Most recently, aza-diarylethenes have been developed in which carbon-carbon bond connections are replaced by carbon-nitrogen connections. This structural elaboration opens up an entire new structure and property space expanding the versatility and applicability of diarylethenes. In this work, we present the second generation of zwitterionic aza-diarylethenes, which finally allows for fully reversible photoswitching and precise control over all three switching states. High-yielding photoswitching between the neutral open form and a zwitterionic Z isomer is achieved with two different wavelengths of light. The third zwitterionic E isomeric state can be reached in up to 87 % upon irradiation with a third wavelength. Its high energy content of >10 kcal/mol can be released thermally by deliberate solvent change as trigger mechanism, rendering aza-diarylethenes into interesting candidates for molecular solar thermal energy storage (MOST) applications. The third state also serves as locking state, allowing to toggle light-responsiveness reversibly between thermally labile and thermally stable switching. Further, irradiation of the zwitterionic states leads to highly efficient photopolymerization of methyl acrylate (MA), directly harnessing the unleashed chemical reactivity of our aza-diarylethene in a materials application.
CRIS-Team Scopus Importer:2024-11-29
Keywords: aza-diarylethene; light-responsive materials; molecular solar thermal energy storage; multi-state switching; Photochromism